Comparison of the protective effects of curcumin and caffeic acid phenethyl ester against doxorubicin‐induced testicular toxicity. (1st December 2020) - Huyut, Zübeyir; Alp, Hamit Hakan; Yaman, Turan; Keleş, Ömer Faruk; Yener, Zabit; Türkan, Fikret; Ayengin, Kemal
Abstract: Whether testicular toxicity is mediated by matrix metalloproteinases (MMPs) is an important question that has not been examined. This study investigated the suppressive effect of curcumin and caffeic acid phenethyl ester (CAPE) on oxidative stress, apoptosis, and whether MMPs mediate doxorubicin (DOX)‐induced testicular injury. Male rats were randomly divided into eight groups ( n  = 8 per group). The groups were as follows: sham, dimethyl sulphoxide (100 µL), DOX (3 mg/kg), CAPE (2.68 mg/kg), curcumin (30 mg/kg), DOX+CAPE (3 mg/kg DOX and 2.68 mg/kg CAPE), DOX+curcumin (3 mg/kg DOX and 30 mg/kg curcumin) and DOX+CAPE+curcumin (3 mg/kg DOX, 2.68 mg/kg CAPE and 30 mg/kg curcumin). Injections were administered daily for 21 days. The oxidative stress, MMPs, proinflammatory cytokines and apoptotic markers in the DOX group were higher than the sham group ( p  < .05); these measures were lower in the groups treated with CAPE and curcumin together with DOX compared with the DOX group ( p  < .05). The results showed that MMPs mediated DOX‐induced testicular injury, but CAPE and especially curcumin suppressed testis injury and cell apoptosis by suppressing DOX‐induced increases in MMPs, oxidative stress and proinflammatory cytokines. However, curcumin exhibited more pronounced effects than CAPE in terms of all studied parameters.